2006
DOI: 10.1200/jco.2005.02.8332
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Symptom Assessment Instruments: A Systematic Review

Abstract: Purpose A variety of assessment instruments have been created to identify cancer symptoms. We reviewed systematically cancer symptom assessment instruments published in English. Methods A systematic search of the MEDLINE database, Cochrane Library, Cumulative Index of Nursing and Allied Health Literature (CINAHL), and EMBASE was performed. Non–peer-reviewed articles were identified through BIOSIS. Articles were accessed through the related article links in PubMed and references were searched by hand. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
189
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(201 citation statements)
references
References 112 publications
3
189
1
8
Order By: Relevance
“…Physical symptoms are commonly dissociated from cognitive and affective symptoms. Previous studies have suggested that 3 symptoms, occurring at the same time, might be considered a cluster, 12,20,21 and several studies demonstrated correlations (tight, close, or frail) between clusters. 22,23 There has been growing awareness that common biologic mechanisms may underlie or contribute to simultaneously reported symptoms 24 and there is clinical evidence that symptoms grouped in a cluster may share a common biologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Physical symptoms are commonly dissociated from cognitive and affective symptoms. Previous studies have suggested that 3 symptoms, occurring at the same time, might be considered a cluster, 12,20,21 and several studies demonstrated correlations (tight, close, or frail) between clusters. 22,23 There has been growing awareness that common biologic mechanisms may underlie or contribute to simultaneously reported symptoms 24 and there is clinical evidence that symptoms grouped in a cluster may share a common biologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that patients with advanced cancer suffer many physical and psychological symptoms, and these issues frequently are not addressed well in conventional care. 8,[23][24][25] In the current study, we characterized the distress symptoms, interventions, and outcomes of patients who were admitted to the ICU and referred to a PCT in a cancer center. We observed that a significant number of ICU patients had severe physical and emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with advanced cancer will develop physical and psychological symptoms related to their disease, treatments, or comorbidities. 2,3 These symptoms, which can significantly impair the patient's quality of life and family dynamics, are infrequently treated in conventional care. Palliative care programs have been developed to fill this gap in care.…”
mentioning
confidence: 99%